2020
DOI: 10.3390/v12091032
|View full text |Cite
|
Sign up to set email alerts
|

Abrogating ALIX Interactions Results in Stuttering of the ESCRT Machinery

Abstract: Endosomal sorting complexes required for transport (ESCRT) proteins assemble on budding cellular membranes and catalyze their fission. Using live imaging of HIV virions budding from cells, we followed recruitment of ESCRT proteins ALIX, CHMP4B and VPS4. We report that the ESCRT proteins transiently co-localize with virions after completion of virion assembly for durations of 45 ± 30 s. We show that mutagenizing the YP domain of Gag which is the primary ALIX binding site or depleting ALIX from cells results in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…For example, ALIX recruitment via a YPXL domain is not essential in HIV-1 budding if a PTAP-TSG101 interaction is present. However, a recent study showed that ALIX is required for the efficient engagement of CHMP4B and VPS4 [ 80 ]. Multiple late domains may also play distinct roles at different stages of the assembly of the same virus.…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%
“…For example, ALIX recruitment via a YPXL domain is not essential in HIV-1 budding if a PTAP-TSG101 interaction is present. However, a recent study showed that ALIX is required for the efficient engagement of CHMP4B and VPS4 [ 80 ]. Multiple late domains may also play distinct roles at different stages of the assembly of the same virus.…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%
“…ALIX is also an essential component of this process and exhibits the same localization pattern, as does ESCRT-I [47]. By binding to a spatially separated L-domain from that of ESCRT-I, ALIX can localize to the budding neck lumen and recruit ESCRT-III directly by virtue of its p6-binding V domain and CHMP4B-binding Bro1 domain, respectively [47][48][49]. Evidence of these structures have been captured in relevant cell types as well as in vitro [44,50,51].…”
Section: A Hexagonal Assembly Of Hiv-1 Gag Drives Particle Maturation and Escrt Recruitmentmentioning
confidence: 99%
“…Each data point represents a cell (n = 8 cells for ALIX, and n = 12 cells for FL EAP45) processed with the pipeline illustrated in, B. Welch's two sample t test was used to compare the colocalisation results from ALIX and Gag, to those of FL EAP45 and Gag subsequent recruitment of other ESCRT components. 14,17 We transfected piGFP into an mCherry-ALIX expressing HeLa cell line. 35 One day post-transfection, the cells were fixed and examined using TIRF microscopy.…”
Section: Spatial Co-occurrence Analysis Using Widefield Tirf Microscopymentioning
confidence: 99%
“…The assembly of Gag particles at the cell membrane during HIV budding has been reported to occur within a time frame of $10 minutes, 11,47 and the dynamics of ESCRT protein recruitment by Gag particles have been reported for TSG101, 11,16 VPS4A, 5,12,15,17 some CHMP proteins of ESCRT-III 5,11 and ALIX, 14,17 with an association time at the membrane for different components varying from as little as a few seconds up to 20 minutes. To further validate the observed association between Gag and EAP45, and to analyse its dynamics, we used TIRF microscopy in live HeLa cells to visualise the spatiotemporal relationship between GFP-Gag and SNAP-FL EAP45 at the plasma membrane.…”
Section: Single Particle Tracking In Live Hela Cells Shows Transient Colocalisation Of Gag and Eap45mentioning
confidence: 99%
See 1 more Smart Citation